2022
DOI: 10.3390/w14020250
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Analysis of a Microalgal-Production Plant for the Transformation of Inland-Fisheries Wastewater in Sustainable Feed

Abstract: The present research evaluates the simulation of a system for transforming inland-fisheries wastewater into sustainable fish feed using Designer® software. The data required were obtained from the experimental cultivation of Chlorella sp. in wastewater supplemented with N and P. According to the results, it is possible to produce up to 11,875 kg/year (31.3 kg/d) with a production cost of up to 18 (USD/kg) for dry biomass and 0.19 (USD/bottle) for concentrated biomass. Similarly, it was possible to establish th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Therefore, the wastewater must be supplemented with an external source of N and P to support the microalgal growth to produce fish feed, which may increase the cost of production. According to early results from our research group, an algal production plant of 500 m 3 using fishery wastewater supplemented with N and P can produce up to 11,875 kg/year (31.3 kg/day) with a production cost of up to 18 USD/kg for dry biomass (dry feed) and 0.19 USD/bottle for concentrated liquid biomass (live feed) [64] In the present study, we sought to determine the concentration of N, P, and carbon that favored biomass production using a nonfactorial response surface design, an interesting tool for optimizing different processes, including algal production [65]. Our results show that the interaction between sodium bicarbonate and the phosphate source improved biomass production; to the best of our knowledge, this is the first report on the…”
Section: Supplemented Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the wastewater must be supplemented with an external source of N and P to support the microalgal growth to produce fish feed, which may increase the cost of production. According to early results from our research group, an algal production plant of 500 m 3 using fishery wastewater supplemented with N and P can produce up to 11,875 kg/year (31.3 kg/day) with a production cost of up to 18 USD/kg for dry biomass (dry feed) and 0.19 USD/bottle for concentrated liquid biomass (live feed) [64] In the present study, we sought to determine the concentration of N, P, and carbon that favored biomass production using a nonfactorial response surface design, an interesting tool for optimizing different processes, including algal production [65]. Our results show that the interaction between sodium bicarbonate and the phosphate source improved biomass production; to the best of our knowledge, this is the first report on the…”
Section: Supplemented Wastewatermentioning
confidence: 99%
“…Therefore, the wastewater must be supplemented with an external source of N and P to support the microalgal growth to produce fish feed, which may increase the cost of production. According to early results from our research group, an algal production plant of 500 m 3 using fishery wastewater supplemented with N and P can produce up to 11,875 kg/year (31.3 kg/day) with a production cost of up to 18 USD/kg for dry biomass (dry feed) and 0.19 USD/bottle for concentrated liquid biomass (live feed) [64].…”
Section: Supplemented Wastewatermentioning
confidence: 99%
“…Largescale production is separated into processes with associated input requirements (energy consumption, nutrients, fresh or sea water, and others). The most common processes are cultivation, dehydration, harvesting, drying, and further processing (extraction, stabilization, and packaging), which has an environmental footprint [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of biological processes include environmental compatibility, competitive cost, non-hazardous metabolites, and reduced water consumption [19]. In recent times, microalgae and cyanobacteria have emerged as sustainable remedies for eliminating harmful substances present in various wastewater types, such as agricultural runoff [20], domestic wastewater [21], agroindustrial wastewaters [22][23][24][25], and landfill leachate [26]. It was reported that Cosmarium species could attenuate malachite green dye at temperatures of 5-45 • C and pH 9, demonstrating its ability to treat wastewater containing this pollutant [27].…”
Section: Introductionmentioning
confidence: 99%